Buck converter design for photovoltaic emulator application - Ayop R.; Tan C.W.; Syed Nasir S.N.; Lau K.Y.; Ling Toh C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric resistance; Light sources; Specifications; Continuous current modes; Control simplicity; Control strategies; Conventional design; Current resistance; Development and testing; Output voltage ripple; Single-diode models; DC-DC converters